PENGATURAN PROSEDUR PEMBATALAN SERTIPIKAT HAK ATAS TANAH YANG MERUPAKAN BARANG MILIK NEGARA - Mahadewi, Anak Agung Istri Diah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Astract This study discusses, "regulation of Procedure Cancellation of Certificate of Land which is the State Owned Assets", which aims to study theoretically on Cancellation of Certificate of Rights to the land including State owned Assets, ie, how the implementation Regulation of Cancellation of Certificate of Land to include of State. This research is a law that is derived from primary and secondary legal materials were then analyzed by using the approach of legislation and legal concepts and approaches using analytical tools and techniques argumetasi legal description. Discussion and research results can be summarized as follows: Regulation Procedure cancellation of Certificate of Land which is the State Owned Assets can not provide legal certainty for the National Land Agency officials in conducting cancellation, because to the state owned assets known as asset removal must be approved by Property Manager the Minister of Finance, while the state owned assets such as land has issued a certificate if the object of the dispute and has permanent legal force in terms of the form of action settlement with the cancellation of the certificate of land Rights. So in this case the absence of a definite regulation that can be used as guidelines for the Government Apparatus to take legal action in the form of cancellation of Certificate of Land Rights
Keywords: Regulation; cancellation of certificate of land rights; state owned assets